2015
DOI: 10.1007/s11276-015-1005-1
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle authentication via monolithically certified public key and attributes

Abstract: Vehicular networks are used to coordinate actions among vehicles in traffic by the use of wireless transceivers (pairs of transmitters and receivers). Unfortunately, the wireless communication among vehicles is vulnerable to security threats that may lead to very serious safety hazards. In this work, we propose a viable solution for coping with Man-in-the-Middle attacks. Conventionally, Public Key Infrastructure is utilized for a secure communication with the pre-certified public key. However, a secure vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 87 publications
0
18
0
Order By: Relevance
“…In addition, the DAPPA protocol is efficient than the ECDSA protocol in [184] and more efficient than the IBA scheme in [55] on average, but lack non-repudiation compared to the PBA scheme in [67]. Based on monolithically certified public key and attributes, Dolev et al [69] proposed an idea to ensuring the countermeasures against the Man-in-the-Middle attack under the vehicle authentication. The work in [69] is efficient in terms of iteration cost compared to other existing Authenticated Key Exchange (AKE) protocols such as ISO-KE [241] and SIGMA [228].…”
Section: Authentication Protocols For Iovmentioning
confidence: 99%
“…In addition, the DAPPA protocol is efficient than the ECDSA protocol in [184] and more efficient than the IBA scheme in [55] on average, but lack non-repudiation compared to the PBA scheme in [67]. Based on monolithically certified public key and attributes, Dolev et al [69] proposed an idea to ensuring the countermeasures against the Man-in-the-Middle attack under the vehicle authentication. The work in [69] is efficient in terms of iteration cost compared to other existing Authenticated Key Exchange (AKE) protocols such as ISO-KE [241] and SIGMA [228].…”
Section: Authentication Protocols For Iovmentioning
confidence: 99%
“…Literature [27] presented an authenticated key exchange protocol for Wireless Body Area Network. Literature [28] presented an authentication and key exchange protocol for Vehicular Networks. Although we mainly focus on privacy preserving profile matching in this paper, using our scheme, the shared key can be exchanged between the matched pair securely and authentically.…”
Section: Related Work and Comparisonmentioning
confidence: 99%
“…According to our previous work [37], we proposed a modified certificate structure for existing IEEE 1609.2 [1, 2, 4] security standard. The IEEE 1609.2 based security infrastructure provides certificate based authentication.…”
Section: Introductionmentioning
confidence: 99%
“…However, we have shown that the naive certificate structure is insufficient to avoid impersonation attacks. In our preliminary work [37], vehicle public key is certified by a Certificate Authority (CA) along with the vehicle static attributes. A certificate recipient must first verify the digital signature over the certificate contents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation